Respuesta :

x + 2y = 3.........(i)
-3x + 4y = -4.....(ii)

From the first equation,    x = 3 - 2y  ......(iii)
Substituting equation (iii) into equation (ii)

-3x + 4y = -4.....(ii)
-3(3 - 2y) + 4y = -4
-9 + 6y + 4y = -4
-9 + 10y = -4
     10y =  -4 +9
      10y = 5      Divide both sides by 10
          y =  5/10
          y = 0.5

Substituting y = 0.5 into  x = 3 - 2y  ......(iii)
                            x = 3 - 2y
                             x = 3 - 2(0.5) = 3 - 1= 2.

x = 2,  y = 0.5
x+2y=3 -3x+4y=-4
x + 2y = 3
    - 2y     -2y

x = 3 - 2y 
-3(3-2y) + 2y = -4

-9 + 6y + 2y = -4
-9 + 8y = -4
+9           +9
8y = 5
y = 0.625 


-3x+4y=-4
-3x + 4(0.625) = -4
-3x + 2.5 = -4
 -3x = -6.5
x = 2.16 

x = 2.16
y = 0.625